Differential Effects of Dietary White Meat and Red Meat on NAFLD Progression by Modulating Gut Microbiota and Metabolites in Rats. (5th August 2022) - Li, Juan; Li, Yuting; Feng, Shufen; He, Kaiyin; Guo, Liliangzi; Chen, Weiwei; Wang, Min; Zhong, Lixian; Wu, Chutian; Peng, Xiaojuan; Tang, Shaohui
Abstract : Objective . To assess the effects of dietary white meat (grass carp and chicken) and red meat (pork and beef) on metabolic parameters, including the intestinal microbiota and its metabolites (SCFAs and bile acids) in NAFLD rats induced by high-fat diet. Methods . NAFLD rats were randomly assigned to five groups: NAFLD group, grass carp group, chicken group, pork group, and beef group (10 rats in each group), and these rats were fed for 8 weeks using the high-fat diet, grass carp-based diet, chicken-based diet, pork-based diet, and beef-based diet, respectively. At the end of the intervention, NAFLD-related metabolic indexes, intestinal flora, and its metabolites were measured. Results . The grass carp-based diet significantly improved hepatic pathological changes and glycolipid metabolism, and the chicken-based diet only partially improved the metabolic parameters. However, NAFLD progression was observed in the pork group and the beef group. What is more, the white meat-based diet-mediated changes in the enrichment of beneficial bacteria (such as Lactobacillus or Akkermansia ), SCFAs, and unconjugated BAs (such as UDCA) and the depletion of pathogenic bacteria (such as Bilophila and Prevotella_9 ) and conjugated BAs were observed, while the red meat-based diet-induced changes in the enrichment of pathogenic bacteria ( Prevotella_9 or Lachnospiraceae_UCG-010 ) and conjugated BAs and the depletion of SCFAs and unconjugated BAs were found. Conclusion . The dietary white meat and red meat modulating gut microbiota and its metabolites may favor and aggravate NAFLD in rats, respectively.